"5W+1H" Component Analysis in Materials Indonesian Reading in SD/MI - Nafizaturrahmi N; Aninditya Sri Nugraheni (Indonesian Journal of Primary Education, 2022)
This article discusses the 5W + 1H components and their analysis in SD / MI reading materials, namely the 2018 revised class VI student book Theme 2 Sub-theme 1. The purpose of this study is to search for the 5W + 1H component to make it easier to examine the main ideas of reading. The research method used is a descriptive qualitative method with content analysis techniques, namely techniques that make inferences that can be imitated and pay attention to the validity of the data in its context. The results obtained were the 5W + 1H component in the reading material for the 6th grade students' revision of 2018 Theme 2, Sub-theme 1, which stated that all components were contained in the reading, but of the four reading materials there were two readings that were difficult to find the 'Why' component.